Índices eritrocitarios para el diagnóstico de anemia gestacional en el cantón Alausí, Chimborazo. - Moyon Gualancañay, Christopher Jeey (2025)
Anemia is a hematological disorder characterized by a decrease in the number of erythrocytes or the concentration of hemoglobin, caused by physiological factors (such as pregnancy), demographic factors (such as living at high altitudes), and socioeconomic factors, particularly in developing countries. During pregnancy, this condition increases maternal and fetal health risks, potentially leading to miscarriages, prematurity, and low birth weight. These outcomes result from a series of physiological changes during pregnancy that contribute to the development of anemia by lowering erythrocyte indices due to increased iron demand, especially in the third trimester. Anemia affects approximately 50% of pregnant women worldwide, while in Ecuador it impacts 14.7% of women of reproductive age. This study assessed erythrocyte indices in the diagnosis of gestational anemia in the Alausí canton, Chimborazo province, aiming to improve the prevention, detection, and management of this condition through actions that address the social determinants of health, promote nutritional education, and ensure access to public health services. A quantitative, non-experimental approach was used, with a prospective, cross-sectional field study design. The study found that in the parishes of the Alausí canton, more than half (57.7%) of the participants were diagnosed with gestational anemia. These findings underscore the importance of implementing prevention and early diagnosis programs in rural areas through hematological analysis of blood samples.